2023
DOI: 10.1111/rec.13919
|View full text |Cite
|
Sign up to set email alerts
|

Goldilocks forbs: survival is highest outside—but not too far outside—of Wyoming big sagebrush canopies

Abstract: In arid and semiarid systems, positive effects of nurse shrubs generally occur immediately underneath and around shrub canopies, creating microsites that can be targeted to promote plant establishment in restoration settings. Alternatively, the best microsites may occur in the interspace zone immediately surrounding nurse shrubs if positive abiotic effects extend beyond nurse shrub canopy boundaries and if competition with nurse shrubs is reduced in that zone. In the Intermountain West, U.S.A., we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…When precipitation was low, we found that planting near canopies had the potential to increase emergence, dependent on site conditions. Meanwhile, other studies suggest that there is no disadvantage to planting near canopies when precipitation is at normal or higher, as being planted near the canopy does not influence the establishment of direct‐seeded (Swanson et al 2021) or transplanted seedlings (Koutzoukis et al 2023). The same risk‐neutral approach does not hold for fungicide coatings; when precipitation is high, fungicide coatings can greatly increase emergence (Hoose et al 2022), but our results indicate that when precipitation is low, encrusting seeds to deliver fungicide may inhibit emergence.…”
Section: Discussionmentioning
confidence: 99%
“…When precipitation was low, we found that planting near canopies had the potential to increase emergence, dependent on site conditions. Meanwhile, other studies suggest that there is no disadvantage to planting near canopies when precipitation is at normal or higher, as being planted near the canopy does not influence the establishment of direct‐seeded (Swanson et al 2021) or transplanted seedlings (Koutzoukis et al 2023). The same risk‐neutral approach does not hold for fungicide coatings; when precipitation is high, fungicide coatings can greatly increase emergence (Hoose et al 2022), but our results indicate that when precipitation is low, encrusting seeds to deliver fungicide may inhibit emergence.…”
Section: Discussionmentioning
confidence: 99%
“…before fire) has not been practiced as a proactive means of increasing their resistance and resilience. Experimental research to test the feasibility of this proactive approach has been under way since 2018 at six locations in the Great Basin region focusing on public lands (Koutzoukis et al 2020), which constitute majority of rangelands in the West.…”
Section: Introductionmentioning
confidence: 99%